2001
DOI: 10.1111/j.1749-6632.2001.tb03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Endothelial and Hematopoietic Stem and Progenitor Cells by Adenovector‐Mediated Elevation of Serum Levels of SDF‐1, VEGF, and Angiopoietin‐1

Abstract: The chemokine stroma-derived factor-1 (SDF-1) is produced within the bone marrow and mediates chemokinesis and chemotaxis on a variety of cell types that express the CXCR4 receptor. SDF-1-responsive cell types include monocytes and macrophages, B and T lymphocytes, platelets and megakaryocytes, and CD34 + cells, including both hematopoietic progenitors and stem cells. We have used intravenous injection of a replication-incompetent adenovector expressing the SDF-1 gene to elevate serum levels of SDF-1 in Balb/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
166
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(174 citation statements)
references
References 20 publications
6
166
0
2
Order By: Relevance
“…Moreover, ELISA showed that CatK deficiency significantly reduced plasma VEGF levels at day 7 after ischaemia in CatK À / À mice compared with CatK þ / þ mice. VEGF has been shown to modulate EPC mobilization from BM to the circulation and to support vasculogenesis 32,33 . More importantly, our observations here show that the reception of CatK þ / þ BM-derived EPC-like MNCs, but not that of CatK À / À BM-derived EPC-like MNCs, rescued blood flow impairment after hindlimb ischaemia in CatK À / À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ELISA showed that CatK deficiency significantly reduced plasma VEGF levels at day 7 after ischaemia in CatK À / À mice compared with CatK þ / þ mice. VEGF has been shown to modulate EPC mobilization from BM to the circulation and to support vasculogenesis 32,33 . More importantly, our observations here show that the reception of CatK þ / þ BM-derived EPC-like MNCs, but not that of CatK À / À BM-derived EPC-like MNCs, rescued blood flow impairment after hindlimb ischaemia in CatK À / À mice.…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that increased levels of bone marrow-derived endothelial progenitor cells in the peripheral circulation of patients with advanced HCC, and a high correlation between serum VEGF levels and levels of circulating endothelial progenitor cells were observed [31] . It has been suggested that platelets aggregate at metastatic sites, due to factors released from metastatic cells and vascular invasion, resulting in microthrombosis, tumor adhesion, and may release VEGF to the circulation [32,33] . Therefore, we considered that in metastatic HCC patient platelet activation was a part of the sources of serum VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…104 Adenoviral delivered hSDF-1a can mobilize bone marrow-derived endothelial stem cells. 105 The ability of chemokines to mobilize endothelial stem cells and the rapidity of mobilization observed via the chemokine axis, suggest that this axis may have utility in mobilizing stem cells for vascular repair. Further characterization studies on the adult stem cell content of mobilized blood may identify other therapeutic potentials for these cells.…”
Section: Utility Of Chemokine Axis-mobilizationmentioning
confidence: 99%